Effect of Different Cryopreservation Regimens on Manifestation of Immune Modulating Activity of Placenta at Development of Adjuvant Artritis - Goltsev, A. N.; Lutsenko, E. D.; Ostankov, M. V. (Problems of Cryobiology and Cryomedicine, 2008)
Dynamics of accumulation CD4+CD25+ T-regulatory cells in lymph nodes has been investigated at development of adjuvant arthritis before and after introduction of placenta cells. The estimation immunomodulatory effect of placenta cells depending on a cryopreservation mode is spent.